THE SURFACE ROUGHNESS VALUE ALTERATION OF ACRYLIC RESIN IMMERSED IN 10% CINNAMON EXTRACT AS A DISINFECTING MATERIAL - Rheni Safira Isnaeni; Indah Puti Sabirin; Valeria Fansuri (Fakultas Kedokteran Gigi Unjani, 2023)
The surface roughness of acrylic denture bases can be a reservoir for food debris and microorganisms. Surface roughness can result from disinfection procedures. Cinnamon (Cinnamomum burmanii) is a spice-producing tree which has aroma and taste and contains active substances that most act as antimicrobials, namely cinnamaldehyde and eugenol, which can be used as disinfectants. The purpose of this study was to determine the change in the value of the surface roughness of acrylic resin after being immersed in 10% cinnamon extract and 0.5% sodium hypochlorite as a disinfectant. The research was experimental. The samples were heat-polymerized acrylic resin plates immersed in 10% cinnamon extract, 0.5% sodium hypochlorite, and distilled water. The results showed a significant difference in the degree of roughness of the acrylic plate immersed in 0.5% sodium hypochlorite solution compared to 10% cinnamon extract. The acrylic plate immersed in cinnamon extract had a minor level of roughness (0,37 µm) compared to the plate immersed in 0.5% sodium hypochlorite solution (0,20 µm). A cinnamon extract of 10% did not affect the roughness of the acrylic plate. DOI : 10.54052/jhds.v3n1.p1-10